Improving Learning Outcomes in Chemistry through Authentic Assessments of Students - Ilham Assidiq; Fitriyanti Sulaiman; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2020)
The goal of the research was to know how to enhance the learning outcome of Chemistry through an authentic evaluation. The topic of the study included 22 students. Data collection was rendered using an authentic assessment aspect involving the assignment of students, the student journal, the review and student actions during the learning process. The results of the analysis have shown that authentic evaluation and treatment could enhance the results of the study of chemistry